Análise da concentração sérica de miostatina e folistatina em pacientes com Dermatomiosite e Polimiosite - Maso, Cintia [UNIFESP] (2020)
Background: dermatomyositis (DM) and polymyositis (PM) are systemic autoimmune myopathies (SAM) characterized by chronic inflammation of the skeletal muscle. Myostatin is a protein of the TGF- ß family that negatively regulates muscle mass and the follistatin is an antagonist of myostatin. Objective: to evaluate the serum concentration of myostatin and follistatin in patients with SAM and to evaluate the correlation of these protein with muscle strength, fatigue, functional capacity, damage index, serum creatine kinase and aldolase and body composition index. Methods: cross-sectional study with 50 patients (34 DM and 16 PM) and 52 age-and gender-matched controls. Myostatin and follistatin were measured by ELISA. The patients were evaluated according to the International consensus guidelines for trials of therapies in the idiopathic inflammatory myopathies (IMACS). Fatigue was evaluated through the fatigue severity scale (FSS), quality of life through the Short-Form Health Survey-36 (SF-36), physical activity level trough the International Physical Activity Questionnaire (IPAQ) and body composition was performed by a dual emission densitometer with an X-ray source (Lunar Radiation Corporation, model DPX, Madison, WI, USA). Results: we found no difference in myostatin (14.15±9.65 vs 10.97±6.77; p=0.131) and follistatin (0.53 ±0.71 vs 0.49±0.60; p=0.968) serum concentration between patients with SAM and controls, respectively. When DM, PM and control groups were analyzed separately, we observed higher serum levels of myostatin in the PM group compared to the control group (16.92 ± 12.07 vs. 10.97 ± 6.77 ng / mL; p=0.036). There was no difference in serum myostatin [10.99 (5.94-37.48) vs. 12.48 (1.51 - 35.44); p=0.861] and follistatin levels [0.40 (0.0-0.89) vs. (0.30 (0.0-2.28); p=0.886] among patients with and without low muscle mass by body composition, respectively. Patients without corticosteroids had higher serum levels of myostatin than controls. There was no correlation between myostatin levels with muscle strength, fatigue, functional capacity, damage index, serum creatine kinase and aldolase. There was a weak negative correlation of follistatin with muscle strength, functional capacity (SF-36), lean mass index (LMI) and lean appendicular mass (LAM) and weak positive correlation with HAQ, with no correlation with other studied variables. Conclusion: myostatin and follistatin serum concentration was not different between patients and controls, with higher myostatin serum level in those patients without corticosteroids. There was a weak negative correlation between follistatin and muscle strength, functional capacity (SF-36), lean mass index and a weak positive correlation with HAQ. The dosage of serum myostatin and follistatin did not seem useful to asses disease activity or as markers of treatment response in patients with MAS.